Protective potential of glutathione peroxidase‐1 gene against cocaine‐induced acute hepatotoxic consequences in mice. Issue 12 (19th July 2018) - Mai, Huynh Nhu; Jung, Tae Woo; Kim, Dae‐Joong; Sharma, Garima; Sharma, Naveen; Shin, Eun‐Joo; Jang, Choon‐Gon; Nah, Seung‐Yeol; Lee, Sung Hoon; Chung, Yoon Hee; Lei, Xin Gen; Jeong, Ji Hoon; et al.
Abstract: Since the cocaine‐induced oxidative stress has been established to lead to hepatotoxicity, we examined the role of the glutathione peroxidase (GPx)‐1 gene in cocaine‐induced hepatotoxicity. Cocaine treatment significantly increased superoxide dismutase activity in as little as 1 hour, with a maximum level at 6 hours in wild‐type mice, while significantly decreasing GPx activity and subsequently inducing oxidative damage (i.e., reactive oxygen species, lipid peroxidation and protein carbonylation). These changes were more prominent in the mitochondrial fraction than in the cytosolic fraction. In contrast, genetic overexpression of GPx‐1 significantly attenuated cocaine‐induced oxidative damage in mice. Cocaine treatment significantly increased alanine aminotransferase and aspartate aminotransferase levels in the serum. Consistently, cocaine significantly enhanced cleaved caspase‐3 expression and intramitochondrial Ca 2+, while significantly reducing mitochondrial transmembrane potential. Cocaine treatment potentiated cleavage of protein kinase C δ (PKCδ ), mitochondrial translocation of PKCδ, cytosolic release of cytochrome c and activation of caspase‐3, followed by hepatopathologic changes. These results were more prominent in GPx‐1 knockout than in wild‐type mice, and they were less pronounced in overexpressing transgenic than in non‐transgenic mice. Combined, our results suggest that the GPx‐1 gene possesses protective potential against mitochondrial oxidative burden, mitochondrial dysfunction and hepatic degeneration induced by cocaine and that the protective mechanisms are associated with anti‐apoptotic activity via inactivation of PKCδ . Abstract : We investigated the role of glutathione peroxidase (GPx)‐1, a major subtype of GPx in response to hepatotoxicity induced by cocaine in mice. We observed that the failure in GPx induction against superoxide dismutase activation mediates cocaine hepatotoxicity, suggesting that the endogenous GPx‐1 gene is involved in a defensive mechanism against the hepatotoxicity. Furthermore, we also found that the overexpression of the GPx‐1 gene protects cocaine‐induced hepatotoxicity in mice via attenuating mitochondrial burdens (oxidative stress and dysfunction) and pro‐apoptotic parameters.